Enterovirus‐A71 exploits peripherin and Rac1 to invade the central nervous system. (19th April 2021) - Lim, Ze Qin; Ng, Qing Yong; Oo, Yukei; Chu, Justin Jang Hann; Ng, Shi Yan; Sze, Siu Kwan; Alonso, Sylvie
Abstract: Enterovirus‐A71 (EV‐A71) has been associated with severe neurological forms of hand, foot, and mouth disease (HFMD). EV‐A71 infects motor neurons at neuromuscular junctions (NMJs) to invade the central nervous system (CNS). Here, we investigate the role of peripherin (PRPH) during EV‐A71 infection, a type III intermediate neurofilament involved in neurodegenerative conditions. In mice infected with EV‐A71, PRPH co‐localizes with viral particles in the muscles at NMJs and in the spinal cord. In motor neuron‐like and neuroblastoma cell lines, surface‐expressed PRPH facilitates viral entry, while intracellular PRPH influences viral genome replication through interactions with structural and non‐structural viral components. Importantly, PRPH does not play a role during infection with coxsackievirus A16, another causative agent of HFMD rarely associated with neurological complications, suggesting that EV‐A71 ability to exploit PRPH represents a unique attribute for successful CNS invasion. Finally, we show that EV‐A71 also exploits some of the many PRPH‐interacting partners. Of these, small GTP‐binding protein Rac1 represents a potential druggable host target to limit neuroinvasion of EV‐A71. SYNOPSIS: Enterovirus‐A71, causing Hand, Foot and Mouth Disease with neurological complications, exploits intermediate neurofilament peripherin to infect neurons. Via this interaction, EV‐A71 gains access to the small GTP‐binding protein Rac1, a potential druggable host target. Surface‐expressed and intracellular peripherin (PRPH) facilitates EV‐A71 entry and replication in neuronal cells. EV‐A71 also exploits PRPH interacting partner Rac1 during infection specifically in neuronal cells. PRPH or Rac1 have no role in HFMD‐linked coxsackievirus A16 infection, rarely associated with neurological complications. Abstract : Enterovirus‐A71, causing Hand, Foot and Mouth Disease with neurological complications, exploits intermediate neurofilament peripherin to infect neurons. Via this interaction, EV‐A71 gains access to the small GTP‐binding protein Rac1, a potential druggable host target.